2002
DOI: 10.1046/j.1365-2036.2002.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of histological gastritis after cure of Helicobacter pylori infection

Abstract: SUMMARYBackground: It is still disputed whether gastric atrophy or intestinal metaplasia improves after the cure of Helicobacter pylori infection. Aim: To clarify the histological changes after the cure of H. pylori infection through a literature survey. Methods: Fifty-one selected reports from 1066 relevant articles were reviewed. The extracted data were pooled according to histological parameters of gastritis based on the (updated) Sydney system. Results: Activity improved more rapidly than inflammation. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 56 publications
2
65
2
2
Order By: Relevance
“…It is controversial whether IM would improve after H. pylori eradication [20]. In our study, histological assessment also showed that the atrophy score and IM in all patients with type 3 patterns were not improved 12 weeks after H. pylori eradication (data not shown).…”
Section: Diagnostic Efficacy Of Magnifying Nbi Endoscopy In the Predicontrasting
confidence: 44%
See 2 more Smart Citations
“…It is controversial whether IM would improve after H. pylori eradication [20]. In our study, histological assessment also showed that the atrophy score and IM in all patients with type 3 patterns were not improved 12 weeks after H. pylori eradication (data not shown).…”
Section: Diagnostic Efficacy Of Magnifying Nbi Endoscopy In the Predicontrasting
confidence: 44%
“…Several reports show that H. pylori eradication leads to improvement of histological gastritis, such as the degree of chronic inflammation for at least several months [20]. Therefore, whether the gastric mucosal pattern seen by magnifying NBI endoscopy reflects these histological changes would be of great interest.…”
Section: Diagnostic Efficacy Of Magnifying Nbi Endoscopy In the Predimentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Hojo et al performed a meta-analysis of reported changes in histological gastritis following H. pylori eradication, and concluded that activity and inflammation are improved, and that gastric mucosal atrophy improves in part, but that it was difficult to analyse intestinal metaplasia due to problems with methodology, including statistics. 24 One reason for the absence of a unified approach to posteradication histological improvement is the lack of uniformity concerning the site of gastric mucosal biopsies and the degree of atrophy or intestinal metaplasia. In the present study, our findings regarding inflammation and activity in the gastric mucosa were Regenerating mucosa Helicobacter pylori similar for specimens taken from the greater curvature of the antrum, greater curvature of the upper corpus and lesser curvature of the mid-corpus, and similar changes were seen post-eradication.…”
Section: Discussionmentioning
confidence: 99%
“…HP eradication is important because intestinal metaplasia progresses to displasia and gastric cancer. After IM development, mucosal acidity changes and HP colonisation decreases, at which point HP eradication stops being useful [19]. Although local healing following IM can be seen in the antrum, there was no healing in the corpus in some reports [20].…”
Section: Discussionmentioning
confidence: 99%